ANALISIS HUKUM KEDUDUKANGENERAL MANAGER DALAM MEWAKILI PERSEROAN BAIK DI DALAM MAUPUN DI LUAR PENGADILAN (STUDI PADA PT PELABUHAN INDONESIA I (PERSERO) MEDAN) - ARIUS PRIMA (PREMISE LAW JURNAL, 2017)
The provisions regarding a director’s power in Indonesia is stipulated in UUPT (the Law on Limited Company) Article 103, its explanation and the company’s article of association. The director’s power shall be subject to the provisions in Article 123 of HIR and SEMA No. 1/1971 in conjunction with SEMA No. 6/1994 regarding Special Power of Attorney. The position of the General Manager of PT.Pelindo I (Persero) was considered as the Branch Head of the port appointed and terminated by the board of directors. The General Manager could represent the company in and out of the court based on the Decree of the General Manager’s Appointment, the power delegation was determined in the director’s decree, and a special power of attorney was granted from the board of directors to represent the company in and out of the court where the details written in the power of attorney. The legal consequence of this power transfer from the Board of Directors to the General Manager to represent the company was that the board of directors was obliged to fulfill the agreement made by the general manager based on his power. Keywords: Position, General Manager, Represent the Limited Company in and out of the court.